Implantation as a Tool for Personalized Medicine: From Genetic Compatibility to Adaptive Technologies - Khusenovich, Mamatkulov Farkhodjon; Isamiddinovich, Khazatov Alisher (Journal of Science in Medicine and Life, 2025)
Do you want to have a beautiful smile and healthy teeth? Don't wait any longer! Modern methods of dental implantation quickly and painlessly restore missing teeth and strengthen your jaw. Modern methods of dental implantation are an effective replacement of missing teeth with new non-removable structures for prosthetics on installed implants. They preserve the functionality and visual aesthetics of the teeth. Prosthetics on implants and the installation of artificial titanium pins are performed using the least traumatic and reliable, safe and convenient methods. Modern technologies of dental implantation allow for recovery in the shortest possible time.